Solving Third Order Three-Point Boundary Value Problem On Time Scales By Solution Matching Using Differential Inequalities (Global Journal of Science Frontier Research, 2012)
We consider the third order boundary value problem associated with the differential equation on time scales on time scales satisfying the conditions We establish the solution of the three point boundary value problem on time scales on [t 1 , σ 3 (t 3 )] by matching solutions on [t 1 , t 2 ] with solutions on [t 2 , 3 (t 3 )].
Keywords: Time scales; boundary value problem; dynamical equation; matching methods